Landscapes in between : environmental change in modern Italian literature and film - Seger, Monica, 1980- (Toronto Italian studies., 2015)
Landscapes in Between analyses Italian authors and filmmakers who turn to interstitial landscapes as productive models for coming to terms with the modified natural environment.